UDK 621.01 Analysis of dependence on the parameters of the angles and loadings of the conveyor shaft and the drum set with a curved pile after cleaning cotton from small impurities.: Anvar Djurayev, Tashkent Textile and Light Industry Institute d.t.s. professor. Uzbekistan. Tashkent. - Nizomov, Temurbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract The article provides a justification of the recommended values based on the analysis of the graphs of dependence of the vibration coverage and loads of the curved pile drum and the angular velocities of the drive shaft on the rotation stiffness and moment of inertia of the belt drive.